Assessing the Risk of Australian Indigenous Sexual Offenders Reoffending: A Review of the Research Literature and Court Decisions - Allan, A.; Parry, C.; Ferrante, Anna; Gillies, C.; Griffiths, C.; Morgan, F.; Spiranovic, C.; Smallbone, S.; Tubex, H.; Wong, S. (Australian and New Zealand Association of Psychiatry, Psychology and Law, 2018)
The assessment of offenders’ risk of reoffending, particularly sexual reoffending, is a core activity of forensic mental health practitioners. The purpose of these assessments is to reduce the risk of harm to the public, but they are controversial and become more contentious when Australian practitioners who want to undertake such assessments in an ethically responsible way must use reliable validated instruments, disclose the limitations of their assessment methods, instruments and data to judicial decision-makers and understand how decision-makers might use their reports. The purpose of this systematic literature review was to explore the practices of Australian practitioners and courts in respect of the assessment of Australian Indigenous male sexual offenders’ risk of reoffending. We could not identify an instrument that has been developed for the assessment of this population group. Australian courts differ in whether they admit and give weight to practitioners’ evidence and opinions based on data obtained with non-validated instruments. We could only identify three possible predictor variables with enough quantitative support to justify including them in an instrument that could be used to assess Indigenous sexual offenders. There is a need for research regarding the validity of the instruments that practitioners use.